2007
DOI: 10.1186/1471-2180-7-14
|View full text |Cite
|
Sign up to set email alerts
|

New probes used for IS1245 and IS1311 restriction fragment length polymorphism of Mycobacterium avium subsp. avium and Mycobacterium avium subsp. hominissuis isolates of human and animal origin in Norway

Abstract: BackgroundMycobacterium avium is an environmental mycobacterium that can be divided into the subspecies avium, hominissuis, paratuberculosis and silvaticum. Some M. avium subspecies are opportunistic pathogens for animals and humans. They are ubiquitous in nature and can be isolated from natural sources of water, soil, plants and bedding material. Isolates of M. avium originating from humans (n = 37), pigs (n = 51) and wild birds (n = 10) in Norway were examined by IS1245 and IS1311 RFLP using new and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
68
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 31 publications
5
68
2
Order By: Relevance
“…This study showed that mycobacteriamia among febrile HIV-infected Ugandan adults accounted for 13% (Ssali et al, 1998). M. avium is also known to be one of the leading causes of infant lymphadenitis worldwide (Coetzer, 2004;Johansen, 2007;Van Ingen et al, 2009). This is in agreement with a study done in Uganda on the cause of cervical lymphadenitis.…”
Section: Non-tuberculous Mycobacteria In Humansupporting
confidence: 82%
“…This study showed that mycobacteriamia among febrile HIV-infected Ugandan adults accounted for 13% (Ssali et al, 1998). M. avium is also known to be one of the leading causes of infant lymphadenitis worldwide (Coetzer, 2004;Johansen, 2007;Van Ingen et al, 2009). This is in agreement with a study done in Uganda on the cause of cervical lymphadenitis.…”
Section: Non-tuberculous Mycobacteria In Humansupporting
confidence: 82%
“…Whereas IS1311 RFLP usually generates clear hybridization patterns, IS1245 RFLP yields complex multiband patterns which are difficult to compare among different experiments and laboratories, mainly because of the heterogeneity in the intensities of the hybridization bands (19,20,42). Recently, an even simpler PCRbased molecular typing method, multilocus variable-number tandem-repeat analysis (MLVA), which is based on mycobacterial repetitive elements called mycobacterial interspersed repetitive-unit-variable-number tandem repeats (MIRU-VNTRs) (14,34,36,37), has been described for M. avium subsp.…”
mentioning
confidence: 99%
“…For epidemiological investigations of MAC, the current reference molecular typing technique is restriction fragment length polymorphism analysis (RFLP) based on the IS1245 (47) and IS1311 (19,20) insertion sequences. Whereas IS1311 RFLP usually generates clear hybridization patterns, IS1245 RFLP yields complex multiband patterns which are difficult to compare among different experiments and laboratories, mainly because of the heterogeneity in the intensities of the hybridization bands (19,20,42).…”
mentioning
confidence: 99%
“…With the discovery of insertion elements in the mycobacterial genome, the determination of M. avium subspecies has since became more precise (Shamputa et al, 2004;Moravkova et al, 2008). MAA is characterised by the presence of 2 to 17 copies of the IS901 insertion sequence (Dvorska et al, 2003;Inglis et al, 2003) and a single copy of IS1245 (Johansen et al, 2007). To the authors' knowledge, no study for the specific identification of MAA in the tissue of naturally infected hens has previously been reported.…”
mentioning
confidence: 93%